Phycocyanin from oxygenic photogranules: A feasible ecofriendly dye for cotton and silk fibers - Vivek Kumar Nair; Abhishek Sahu; Saurabh Samuchiwal; Anushree Malik; Pooja Ghosh; Bhupendra Singh Butola (Cleaner Materials)
This study investigated the extraction and application of phycocyanin from a novel biomass source, oxygenic photogranules. The results show that optimal phycocyanin extraction (104.69±3.8 mg/g) was achieved using freeze-thawing with extraction solvent as sodium phosphate buffer, followed by 15 min of ultrasonication. Furthermore, ammonium sulphate stabilised extracted phycocyanin was found to be suitable for its long-term storage. Also, dyeing by double mordanting followed by the cold dyeing process showed cotton’s superior phycocyanin affinity (dye adsorption: 55.5±2.8 mg/g) compared to silk (dye adsorption: 31.32±1.09 mg/g). Furthermore, during the wash test, cotton retained a higher colour (64.97%) even after 5 washes when compared to silk (44.43%). Although on analysing the functionality of the fabric, the silk exhibited higher antioxidant activity (93.93±1.76 %) than cotton (64.78±3.06 %). However, in the case of UV protection, cotton demonstrated excellent UV protection with an ultraviolet protection factor (UPF) value of more than 200 when compared to the silk’s UPF of ∼35. These findings underscore the potential of phycocyanin from oxygenic photogranules as a sustainable and functional natural dye for textile fibers.